2015
DOI: 10.1016/j.alit.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of airflow limitation using a new modality of lung sound analysis in asthmatic children

Abstract: It was possible to evaluate airway dysfunction of asthma using ic700, which was calculated non-invasively by analyzing lung sounds alone, without measuring body size and airflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
(1 reference statement)
1
16
0
Order By: Relevance
“…As for the next problem, non‐paroxysmal lung sounds are affected by individual differences such as body size and airflow. We confirmed that the ic700 was not affected by individual differences when using only lung sound data . Next, which is the index that is the most appropriate for the management of asthmatic small children?…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…As for the next problem, non‐paroxysmal lung sounds are affected by individual differences such as body size and airflow. We confirmed that the ic700 was not affected by individual differences when using only lung sound data . Next, which is the index that is the most appropriate for the management of asthmatic small children?…”
Section: Discussionsupporting
confidence: 61%
“…These studies of breath sounds in asthmatic conditions have demonstrated that breath sounds are affected by changes in generation or transmission . We reported in 2009 that the intensity of inspiratory lung sounds reflects airway obstruction in asymptomatic asthmatic children . When the intermediate‐frequency components of lung sounds are transferred to the chest wall, the ic700 increases, implying that there is asthmatic airway dysfunction even when children are asymptomatic.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There have been reports that breath sound frequency components were correlated with the extent of airway obstruction as assessed by an airway hyperresponsiveness test, even in the absence of wheezing 4,5. Other studies have reported that inspiration sound pressure at 700 Hz increased with the severity of bronchial asthma in children without wheezing, demonstrating a significant correlation of the sound pressure at 700 Hz with the forced expiratory volume in 1 second/forced vital capacity (FEV 1.0 /FVC) ratio and the maximal expiratory flow rate at 50% of the vital capacity (FEF 50% predicted) 6. However, little information is available on the correlation between airway inflammation and lung sounds in bronchial asthma patients.…”
Section: Introductionmentioning
confidence: 98%